Student Perceptions of the Sub Element of Integrity: Case Study at University Malaysia Pahang - Shahidah, Hamzah; Muhammad Nubli, Abdul Wahab; Hanina, H. Hamsan (International Journal in Management and Social Science, 2014)
This study aims to key out the perceptions on the integrity of the elements that comprise the discipline, responsibility and honesty. This study used a survey method using questionnaires. 138 respondents were chosen through random sampling. Data were analyzed descriptively involves measuring the mean, standard deviation and correlation. The results showed that a large number of respondents indicated that the factor of integrity takes on a significant role in the forming of individual identity. These components need to be raised from time to time so that positive values will not vanish from the psyche.